2000
DOI: 10.1073/pnas.97.22.12380
|View full text |Cite
|
Sign up to set email alerts
|

Failure to handle more than one internal representation in visual detection tasks

Abstract: Perceptual studies make a clear distinction between sensitivity and decision criterion. The former is taken to characterize the processing efficiency of the underlying sensory system and it increases with stimulus strength. The latter is regarded as the manifestation of a subjective operation whereby individuals decide on (as opposed to react reflexively to) the occurrence of an event based on factors such as expectation and payoff, in addition to its strength. To do so, individuals need to have some knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 12 publications
(6 reference statements)
8
115
2
Order By: Relevance
“…Hence, observers do not place their criteria optimally when handling two different tasks. This decisional behavior in the DD tasks replicates the behavior observed in previous studies with close to threshold stimuli (i.e., where performance was limited by internal noise only; Gorea & Sagi, 2000, thereby generalizing the notion of "criteria attraction" to the case where performance is limited by external noise. To verify that these criteria shifts are due to decisional processes per se and not to responses to the unprobed blob, we measured linear correlations between P("High") and the unprobed blob amplitude, finding r < .09 across all conditions and observers (see the Appendix, Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Hence, observers do not place their criteria optimally when handling two different tasks. This decisional behavior in the DD tasks replicates the behavior observed in previous studies with close to threshold stimuli (i.e., where performance was limited by internal noise only; Gorea & Sagi, 2000, thereby generalizing the notion of "criteria attraction" to the case where performance is limited by external noise. To verify that these criteria shifts are due to decisional processes per se and not to responses to the unprobed blob, we measured linear correlations between P("High") and the unprobed blob amplitude, finding r < .09 across all conditions and observers (see the Appendix, Fig.…”
Section: Resultssupporting
confidence: 83%
“…Given that the internal response is monotonically related to stimulus contrast (for contrast > 0), a comparison between criteria expressed in stimulus luminance units maps onto the comparison of the corresponding internal evoked responses. Hence, in contrast to previous experiments that could not discriminate between criteria equality being due to a uc or to an FA equality (Gorea & Sagi, 2000Kontsevich et al, 2002), the present external-noise paradigm does permit such a distinction. This is so because the performance-limiting noise, σ EX , is known and can be manipulated; given that, in the present conditions, c 0 zFA × σ EX (assuming σ EX >> σ IN ) observers cannot equalize at the same time their FA rates and c when facing two tasks with a different σ EX .…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The main idea of the modeling was that, if constant decision criteria between conditions are assumed (Gorea and Sagi 2000), then one expects different effects of decreased signal strength and increased variability. Figure 3B depicts visually a situation where a subject discriminates between two stimulus alternatives (i.e., S1 vs. S2).…”
Section: Resultsmentioning
confidence: 99%
“…The last assumption is justified by our use of a wagering procedure that encourages constant placement of decision criteria, as well as by previous research that demonstrated that subjects used unified decision criteria for different conditions within an experiment, even when such unified criteria were clearly suboptimal (Gorea and Sagi 2000).…”
Section: Subjectsmentioning
confidence: 99%